Control of an Isolated Ac-Dc Matrix Converter for Vehicle-To-Grid Applications - Diaz-Diaz, M; Vidal-Nunez, C; Rajendran, S (Institute of Electrical and Electronics Engineers Inc., 2022)
Fast electric vehicle chargers are commonly equipped with medium frequency transformers to provide galvanic isolation between the battery and the grid. Conventionally, several Alternating Current (AC) to Direct Current (DC) conversions are needed to insert the medium frequency transformer in the AC-DC grid-battery rectification process. Therefore, this paper presents an electric vehicle charger based on an isolated AC-DC Matrix Converter. A Space Vector Modulation technique is combined with Phase-Shifted Modulation to regulate the power transference at the same time as the proposed charger provides Vehicle-to-Grid services. Simulation results are presented to validate the effectiveness of the proposed topology and control strategy. © 2022 IEEE.